Next-Generation UV: Evaluation of a Robotic Ultraviolet-C Room Disinfection Device. (4th October 2017) - Cadnum, Jennifer; Piedrahita, Christina; Jencson, Annette; Mathew, J Itty; Donskey, Curtis J
Abstract: Background: Mobile ultraviolet-C (UV-C) light room decontamination devices are commonly used as an adjunct to standard cleaning in healthcare facilities. However, the efficacy of UV-C is significantly reduced at increased distance from the device and by shadowing. Methods: In hospital rooms, we compared the efficacy of a standard UV-C room disinfection device operated in one location and a robotic, UV-C device with 3 adjustable lamps that automatically navigates around the patient room to minimize distance from the device and shadowing. The test organisms were methicillin-resistant Staphylococcus aureus (MRSA) and Clostridium difficile spores in 5% fetal calf serum on steel disk carriers that were placed in multiple locations in hospital rooms and exposed to 10 minute UV-C cycles. For the robotic device, we evaluated a 10-minute stationary cycle positioned adjacent to the bed and a mobile cycle in which the unit was programed to navigate the room. Results: As shown in the figure, the robotic device operated in a stationary position was as effective as the standard device against organisms in close proximity to the device (~2–3 feet from the device), but significantly less effective at greater distances. However, operating the robotic device with the mobile cycle significantly improved performance, resulting in a ≥3.0 log reduction in C. difficile spores and MRSA at all sites tested. Conclusion: A robotic UV-C device programed to automatically navigate the room was effective in reducing contamination at sites throughout the room. Disclosures: All authors: No reported disclosures.